Representações sociais de alunas do ensino fundamental sobre bullying - KIMURA, Patrícia Rodrigues de Oliveira (Universidade Federal do Pará, 2013)
This study aims to investigate the social representations of the 8th grade students of elementary school about the bullying phenomenon and its implications in the schooling process. The problem of the research focused on the social representations of students about bullying. The subjects are female students, aged between 13 and 18 years, regularly attending three classes of 8th grade of middle school in a state school. The locus of the research was an institution of middle and high school in the city of Castanhal, located in the northeastern state of Pará. The objectives of the study were the following ones: a) identify and describe, having as basis the consensual thought of middle school youth, the images and the meanings they have about the intimidation, assault and /or harassment, characterized as bullying b) Check the situations in which bullying occurs and which forms are most frequently used among female students c) highlight the causes that contribute to the practical assertion of bullying in the school environment and its consequences; d) Highlight the perceptions of students about the implications of bullying in the schooling process, e) Demonstrate the objectifications and the basis that are part of the process construction of social representations of young people about bullying. The study had a qualitative approach and had as theoretical reference the Moscovici (1978) and Jodelet (2001) Theory of Social Representations. Among the theoretical references used, it is included: Abramavay (2003), Beaudoin and Taylor (2006), Boneti and Priotto (2009), Constantine (2004), Fante (2005), Lopes Neto and Saavedra (2003), Nascimento (2006; 2011), Middelton-Moz and Zawadski (2007), e Silva (2010). The instruments used for data collection were the semi-structured questionnaire and group interview. The data was based on content analysis according to the approach proposed by Franco (2003). The results indicated that the social representations of students about bullying, and they were violent treatment, whose image is based on verbal, psychological and physical aggression; Threat and invisibility, whose image is constituted by the following elements: difference, intolerance, disrespect , envy, competition and rivalry; Contradiction that matches the image of the school as a learning space that becomes weak before the spread of violence; Family and school education that matches the image of the role of family and school as instances that share responsibility for the guidance and training of students. The implications of school evidenced from the social representations of female students about bullying lead to negative repercussions in the schooling process, among which: learning difficulties, low school performance, absenteeism and school evasion.